Toolbox talks to prevent construction fatalities: Empirical development and evaluation. (July 2016) - Olson, Ryan; Varga, Alexandra; Cannon, Annie; Jones, Jamie; Gilbert-Jones, Illa; Zoller, Erika
Highlights: Three studies were conducted to develop and evaluate construction fatality talks. Compared to photos, line drawings increased the distance to identify hazards. New toolbox talk format saved time and was preferred by 82% of supervisors. Scripted talks can make it easier to share fatal stories and prevention strategies. Abstract: Three studies were conducted to develop and evaluate safety toolbox talks about fatal construction incidents. Study 1 surveyed workers ( n = 28) about existing pre-shift meetings. An evidence-based structure for toolbox talks was developed, and study 2 evaluated our selected line drawing illustration format with workers ( n = 30). Study 3 evaluated supervisors' talks using: (1) new toolbox guides and (2) long-form investigation reports with workers from eight construction crews. In study 1, 25% of the sample reported never conducted safety meetings. In study 2, compared to photos, line drawings increased the distance workers' could correctly identify hazards by over 1.5 m. In study 3, the new format was preferred by 82% of supervisors, saved them 15 min preparation/presentation time, and produced favorable impacts with workers. Brief scripted toolbox talks made it easier for supervisors to share fatal stories and prevention recommendations with their crews. When the format includes scripted text for the supervisors, prompts for discussion and action items, and line drawings worker understanding can be enhanced.